Onyx the fortuitous and the talisman of souls [videorecording (Blu-Ray)] - Bowser, Andrew; Bowser, Andrew; Dudley, Olivia Taylor; Combs, Jeffrey, 1954-; Crampton, Barbara, 1962-; Carson, Terrence T.C; Myrin, Arden (Cineverse, 2023)
Onyx the Fortuitous is struggling to find purpose with his soul-devouring side gig when he receives a coveted invitation to the mansion of his idol, Bartok the Great. Here, he joins Bartok and his mysterious delegation to raise the spirit of an ancient demon for a once-in-a-lifetime ritual.